Implementation of Online Learning Daily Evaluation in Higher Education (Universitas Negeri Semarang, 2018)
The research was distributed online by using online assessment that prove an effectiveness.Â if it applied on 21st century learning. The purpose of this research is to uncover the extent of the benefits of using online learning evaluation in higher education seen from the indicator 1.) Implementation of online learning at College, 2). Daily evaluation process regarding online learning at higher education. The method used is descriptive data with qualitative, qualitative data was extracted and performed data analysis using the technique of triangulation. Delights of the descriptive data presented as the interpretation of the results of research which facilitates readings manually. The research results showed that the majority of universities in Central Java have already implemented online evaluations, online evaluation process prepared cooked through evaluation document that will be loaded online. The benefits of this research can be used as material for the study of theory to apply online evaluation on learning in college. The impact of this research is to gain his insight regarding the benefits of strategy evaluation for technology-based teaching lectures in college.